“Surviving against the odds. The impact of peer support workers on a chronically suicidal adolescent in secure residential youth care: a single case report from the Netherlands” - Shireen P. T. Kaijadoe; Karin S. Nijhof; Helen Klip; Arne Popma; Ron H. J. Scholte (International Journal of Qualitative Studies on Health & Well-Being)
Background The use of peer support workers to support suicidal adolescents is underdeveloped. This study focuses on the effects of a one-year intervention with peer support workers on a chronically suicidal adolescent residing in a secure residential youth care facility in the Netherlands. Moreover, we explore the mechanisms that underpin the role of peer support workers in detail. Method This study employed a single case study design. We conducted seven semi-structured interviews with staff, peer support workers, and a chronically suicidal adolescent. The interviews were analysed using a thematic analysis. Results The results indicate that the suicidal tendencies of the adolescent decreased significantly one year after the peer support intervention compared to the initial baseline. Working mechanisms that underpinned the peer support intervention emphasized building meaningful and trust-based relationships, providing recognition and hope, and practical support from a recovery-oriented perspective. Conclusion The results suggest that peer support has a beneficial impact on the adolescent and treatment teams. Peer support workers contribute to a sense of belonging and connection, coping with suicidality, rediscovering life goals, and improving adolescent self-management. Barriers and facilitators to implementing peer support workers are also discussed.